Alpha-Ta / alpha-Ta-N coating with high bearing capacity and high binding force and preparation method thereof

By using alternating layer structure and solid solution phase α-Ta-N layer in α-Ta coating, combined with Arc Enhanced Glow Discharge and High Power Impulse Magnetron Sputtering technology, the brittleness and columnar crystal problems of α-Ta coating are solved. A α-Ta/α-Ta-N coating with high load bearing, high binding force and low brittleness is achieved.

CN119194387AActive Publication Date: 2024-12-27UNIV OF SCI & TECH BEIJING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411478372.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a high load-bearing, high binding force and low brittleness α-Ta coating, especially in the coating, the single structure of α-Ta is difficult to maintain, and the columnar crystal characteristics lead to deterioration of the brittleness and performance of the coating.

Method used

Alternating layer structures are used to ensure the α-Ta-N coating, where the α-Ta- and α-Ta-N layers are deposited by Arc Enhanced Glow Discharge and High Power Impulse Magnetron Sputtering technology As a solid solution phase, columnar crystal characteristics are avoided and high hardness and plasticity are achieved through appropriate N element content and atmosphere control.

Benefits of technology

High hardness (800~1800 HV), high binding force (scratch binding force Lc2>60 N) and low brittleness are achieved, which avoids cracks and cracks of the coating under high loads, and enhances the stability of the coating and Coordinated deformation capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194387A_ABST
    Figure CN119194387A_ABST
Patent Text Reader

Abstract

The invention provides a high-bearing and high-binding-force alpha-Ta / alpha-Ta-N coating and a preparation method thereof, and relates to the field of physical vapor deposition. The alpha-Ta / alpha-Ta-N coating comprises a base layer and an alternating layer, and the alternating layer is connected with the base body through the base layer. The alternating layers are formed by alternating alpha-Ta layers and alpha-Ta-N layers, and the number of the alternating layers is larger than or equal to 6; the crystal structures of the alpha-Ta layer and the alpha-Ta-N layer are both single body-centered cubic structures, and the alpha-Ta-N layer is free of columnar crystal characteristics and is a solid solution phase. Compared with the prior art, the alpha-Ta / alpha-Ta-N coating with high strength, high binding force and high toughness can be obtained through trace gas doping and simple alternate deposition under the conditions of low temperature, no expensive gas (only argon, nitrogen and hydrogen are used), no post-heat treatment and heterogeneous metal bottoming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of physical vapor deposition, specifically to a high-load-bearing and high-adhesion α-Ta / α-Ta-N coating and its preparation method. Background Technology

[0002] Bulk tantalum (Ta) metal possesses excellent physical and chemical properties, including a high melting point, high corrosion resistance, high ductility, and excellent biocompatibility. During coating preparation, Ta coatings exhibit two distinct crystal structures: body-centered cubic α-Ta and tetragonal β-Ta. The former, similar to bulk Ta, exhibits excellent ductility but lower hardness and poor wear resistance. The latter possesses higher hardness, leading some researchers to believe it holds great promise for wear resistance. However, practical applications and research have revealed that β-Ta exhibits extremely high brittleness, with adjacent interfaces becoming weak points in the coating. Under external forces or even internal stresses within the coating, sudden brittle fracture is possible. Currently, there is a general consensus in the academic community that α-Ta holds greater promise for applications. However, achieving a single α-Ta structure remains a significant challenge.

[0003] To address the issue of α-Ta being too soft, some researchers have proposed using Ta x N y The compounds alternately enhance each other. But Ta x N y The compounds have extremely complex compositions, with more than ten reported so far. Most are face-centered cubic, hexagonal close-packed, or tetragonal structures. On the one hand, they all exhibit considerable brittleness; on the other hand, their crystal structures differ significantly from α-Ta. To date, due to the brittleness and other issues associated with these compounds, the film-substrate adhesion and fracture toughness of alternating coatings have failed to meet requirements. How to achieve non-phase-transformation, low-brittleness strengthening of α-Ta remains unreported.

[0004] Meanwhile, α-Ta and β-Ta exhibit columnar crystal characteristics during coating deposition, and under certain processes, they can even grow into coarse columnar crystals. Continuous columnar grain boundaries are a defect. On the one hand, continuous grain boundaries can provide a rapid channel for the inward diffusion of oxidizing atmosphere; on the other hand, they are prone to causing coating cracking under external forces. Therefore, through-type columnar crystals are not conducive to the use of coatings under oxidizing atmospheres and high loads.

[0005] Due to the aforementioned problems, there is an urgent need to obtain α-Ta / α-Ta-N coatings with high load-bearing capacity, high toughness, and high adhesion. Summary of the Invention

[0006] To address the above problems, this invention provides a high load-bearing and high-adhesion α-Ta / α-Ta-N coating and its preparation method.

[0007] A high-load-bearing and high-adhesion α-Ta / α-Ta-N coating, wherein,

[0008] 1) The α-Ta / α-Ta-N coating includes an underlayer and an alternating layer, wherein the alternating layer is connected to the substrate through the underlayer;

[0009] 2) The alternating layers are composed of alternating α-Ta layers and α-Ta-N layers, and the number of alternating layers is ≥6;

[0010] 3) The crystal structures of the α-Ta layer and the α-Ta-N layer are both single body-centered cubic structures. The α-Ta-N layer has no columnar crystal characteristics and is a solid solution phase.

[0011] Compared with the heterocrystalline structure Ta widely adopted in existing technologies x N y Unlike compound ceramic layers, the α-Ta-N layer in this application has the same crystal structure as the α-Ta layer. The Ta-N layer is a special solid solution phase with a higher nitrogen content than in the equilibrium phase diagram, which can achieve better overall performance in terms of hardness and plasticity.

[0012] Preferably, the grain size of the columnar crystals in the horizontal cross-section of the α-Ta layer gradually increases from the direction near the substrate to the direction away from the substrate, and the columnar crystals in the α-Ta layer are completely broken by the α-Ta-N layer, without extending into the α-Ta-N layer or adjacent Ta layers. This feature indicates that the coating is located in the "T region" (a non-uniform V-shaped grain structure across the entire film thickness) in the film's crystal structure. In this region, gaps at grain boundaries are avoided, as are performance degradation caused by coarse columnar crystals. Furthermore, breaking the columnar crystals is more significant in this crystal structure region, enabling controllable grain size in both the horizontal and vertical directions. For columnar crystals in other crystal structure regions, grain breaking only reduces the grain size in the vertical direction. However, for columnar crystals, due to their special structure, reducing their grain size in the horizontal direction is more meaningful.

[0013] Preferably, the α-Ta / α-Ta-N coating has a hardness of 800-1800 HV, a scratch bonding force Lc2 > 60 N, and no radial cracks in the Vickers indentation of the coating at 10 kgf.

[0014] Preferably, the lattice mismatch between the α-Ta layer and the α-Ta-N layer is <3%. A smaller lattice mismatch results in lower interfacial energy, significantly reducing local stability. This effectively increases the bonding force and stability of the interlayer interface. Furthermore, it can also enhance the cooperative deformation capability of the two layers.

[0015] Preferably, the nitrogen (N) content in the α-Ta-N layer is 1.0–9.9 at%. This application combines a suitable N content with a special preparation method, allowing the N in the coating to exhibit a solid solution state (i.e., unsaturated, saturated, and supersaturated). Through solid solution strengthening, an effect similar to martensite in steel is achieved. High hardness is obtained while maintaining the original crystal structure. Furthermore, maintaining the original crystal structure further ensures a relatively small degree of lattice mismatch.

[0016] Preferably, the thickness ratio of the α-Ta layer to the Ta-N layer is (1-8):1, the hardness of the α-Ta layer is 500-750 HV, and the hardness of the Ta-N layer is 1500-2800 HV. A sufficiently thick α-Ta layer can absorb mechanical energy through elastoplastic deformation under external force, slowing the initiation and propagation of cracks. A suitable Ta-N layer can provide support for the overall coating. If the proportion of the Ta-N layer is too high, the coating will become too brittle, thus reducing its fracture toughness and adhesion; if the proportion of the Ta-N layer is too low, it will not provide sufficient resistance to deformation, resulting in reduced hardness.

[0017] Preferably, the crystallinity of the α-Ta-N layer is lower than that of the α-Ta layer. On the one hand, nitrogen (N) can provide additional nucleation sites, resulting in finer grains in the α-Ta-N layer. On the other hand, the addition of nitrogen causes lattice distortion and increases dislocation density, thus affecting the crystallinity of this layer. The presence of localized amorphous areas can further enhance the hardness of the α-Ta-N layer, giving the α-Ta-N layer in its solid solution state a hardness similar to that of the compound phase.

[0018] The method for preparing the high load-bearing and high-adhesion α-Ta / α-Ta-N coating as described above includes the following steps:

[0019] S1. Cleaning: The substrate material is cleaned using plasma cleaning technology, specifically Arc Enhanced Glow Discharge (AEGD).

[0020] S2. Underlayer Deposition: High-Power Impulse Magnetron Sputtering (HiPIMS) combined with Direct-Current Magnetron Sputtering (DCMS) is used to prepare the underlayer using a tantalum target with a purity ≥99.95 wt%. The deposition atmosphere pressure is 0.5–1.0 Pa, and the target peak power density is ≥1800 W / cm³. 2 ;

[0021] S3, Alternating Layer Deposition: Using HiPIMS superimposed DCMS technology, a tantalum target with a purity ≥99.95 wt% is used to prepare the coating substrate. The bias voltage is less than that of S2, the deposition atmosphere pressure is 0.5–1.0 Pa, and the target peak power density is ≥1800 W / cm³. 2 .

[0022] Preferably, in S1, the plasma cleaning temperature is ≤200 ℃, the time is 5–20 min, the ratio of anolyte current to cathode current in AEGD is greater than 1, and the atmosphere is argon or a combination of argon and hydrogen. Compared to other processes, the plasma source in AEGD is farther from the sample. This results in an ultra-high density of low-energy plasma near the substrate, reducing the risk of arcing while achieving cleaning. Cleaning the substrate surface is more conducive to maintaining the bcc lattice of the bulk material itself during the underlayer cleaning, obtaining a single α-Ta.

[0023] Preferably, in S2, the average current ratio of DCMS / HiPIMS is ≤0.8, the temperature is ≤200 ℃, the bias voltage is 400~1000 V, and the atmosphere is argon. This application combines HiPIMS and DCMS to increase the deposition rate while enhancing the plasma density. Combined with pulsed bias technology, the total particle energy bombarding the substrate surface per unit time can be increased, which helps to obtain single α-Ta. The preferred ratio of DCMS to HiPIMS ensures that the crystal type remains heterogeneous with HiPIMS, while the total amount of ionized ions and the deposition rate can be controllably improved.

[0024] Preferably, in S3, the average current ratio of DCMS / HiPIMS is ≤0.8, the temperature is ≤350 ℃, the bias voltage is 0~300V, and the target-substrate distance is 80~100 mm.

[0025] Preferably, in S3, the deposition of Ta and Ta-N layers is achieved by adjusting the ratio of nitrogen to argon. The deposition atmosphere of the Ta layer is argon, and the deposition atmosphere of the Ta-N layer is a mixture of argon and nitrogen.

[0026] Further preferably, in the mixed atmosphere of argon and nitrogen, the flow ratio of argon to nitrogen is 75:1-100:1. The lower nitrogen content, combined with the ionization rate of DCMS / HiPIMS, allows for precise control of nitrogen solid solution. The lower nitrogen concentration also effectively prevents the formation of Ta-N compounds due to plasma nitriding.

[0027] More preferably, the thickness of the α-Ta and α-Ta-N layers can be achieved by adjusting the time interval range of nitrogen gas introduction, with the time ratio of no nitrogen gas introduction to nitrogen gas introduction being (1~8):1.

[0028] The key technical points and beneficial effects of this invention are as follows:

[0029] (1) Low lattice mismatch design: By designing a single α-Ta and α-Ta-N solid solution, adjacent layers have the same lattice type, thereby achieving low lattice mismatch between layers. This results in lower interlayer interface energy, better stability, and cooperative deformation capability.

[0030] (2) Preferred strengthening method: Unlike the heterogeneous strengthening of traditional hard layers using ceramic or intermetallic compound phases, this invention uses a strengthening mechanism that combines solid solution, fine grains, and localized amorphous structures to construct the α-Ta-N layer. This enhances the strength of the coating while preserving the ductility and toughness of α-Ta as much as possible. At the same time, by optimizing the columnar crystal type (grain size gradually increases from bottom to top), the crystal size in both the horizontal and vertical directions can be precisely controlled.

[0031] (3) The three-in-one approach of cleaning discharge mode, deposition discharge mode, and deposition discharge atmosphere: A highly clean surface is obtained through AEGD, and high energy flux is obtained through high bias voltage combined with DCMS / HiPIMS, which work together to obtain a single α-Ta layer. The high ionization rate of DCMS / HiPIMS combined with a discharge atmosphere with a low N concentration achieves controllable solid solubility while avoiding the formation of surface nitride phases. At the same time, through the special form of ionization-bombardment, a higher temperature gradient than traditional nitriding is achieved, forming a martensitic phase transformation effect in steel and realizing a supersaturated Ta-N solid solution. The three-in-one approach ensures the controllable realization of low lattice mismatch design and optimized strengthening mode. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 The XRD pattern is shown in Example 1.

[0034] Figure 2 The coating section of Example 1 is a secondary electronic phase;

[0035] Figure 3 This is a cross-sectional HRTEM image of Example 1;

[0036] Figure 4 The image shows the HRC indentation pattern at 150 kgf in Example 1.

[0037] Figure 5 The 10 kgf Vickers indentation of Example 1;

[0038] Figure 6 The image shows the HRC indentation pattern at 150 kgf in Example 2.

[0039] Figure 7 The 10 kgf Vickers indentation of Example 2;

[0040] Figure 8 The HRC indentation diagram at 150 kgf is shown in Comparative Example 1.

[0041] Figure 9 The image shows the HRC indentation pattern at 150 kgf for Comparative Example 2. Detailed Implementation

[0042] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0043] Example 1

[0044] A high load-bearing and high-adhesion α-Ta / α-Ta-N coating, wherein the α-Ta / α-Ta-N coating comprises an underlayer and an alternating layer, the alternating layer being connected to the substrate through the underlayer;

[0045] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 18 alternating layers; the thickness of a single α-Ta layer is 1000 nm and the thickness of a single α-Ta-N layer is 500 nm.

[0046] The method for preparing the high load-bearing and high-adhesion α-Ta / α-Ta-N coating includes the following steps:

[0047] S1. Cleaning: The substrate material is plasma cleaned using AEGD technology; temperature 200 ℃, time 15 min, anolyte current 80 A, cathode current 70 A, atmosphere is argon.

[0048] S2. Underlayer Deposition: The underlayer was prepared using HiPIMS superimposed DCMS technology and a 99.99 wt% pure tantalum target. The deposition atmosphere pressure was 0.6 Pa, and the target peak power density was 2600 W / cm³. 2 The average current ratio of DCMS / HiPIMS was 0.5A:0.8A, the temperature was 200 ℃, the bias voltage was 500 V, and the atmosphere was argon.

[0049] S3, Alternating Layer Deposition: The coating substrate was prepared using HiPIMS superimposed DCMS technology and a 99.99 wt% pure tantalum target. The bias voltage was lower than that in S2, the deposition atmosphere pressure was 0.65 Pa, and the target peak power density was 2600 W / cm³. 2The average current ratio of DCMS / HiPIMS was 0.5A:0.8A, the temperature was 200 ℃, the bias voltage was 100 V, and the target-substrate distance was 90 mm. The deposition atmosphere for the α-Ta layer was argon, and the deposition atmosphere for the α-Ta-N layer was a mixture of argon and nitrogen.

[0050] In S3, the deposition of α-Ta and α-Ta-N layers is achieved by adjusting the ratio of nitrogen to argon (80:0 and 80:1). In the mixed atmosphere of argon and nitrogen, the flow rate ratio of argon to nitrogen is 80:1. The time without nitrogen introduction is 10 min, and the time with nitrogen introduction is 5 min.

[0051] Figure 1 The XRD pattern of the α-Ta / α-Ta-N coating prepared in Example 1 shows that the X-ray diffraction patterns of the α-Ta layer and the α-Ta-N layer are the same, and the crystal structures of the α-Ta layer and the α-Ta-N layer are both body-centered cubic structures.

[0052] Figure 2 The figure shows the secondary electronic phase of the coating cross-section in Example 1. The transversely continuous columnar region in the figure is the α-Ta layer, and the other regions are the α-Ta-N layers. Figure 2 The α-Ta layer shown is columnar crystal, while the α-Ta-N layer does not have columnar crystal characteristics. The grain size of the columnar crystal in the horizontal cross section of the α-Ta layer gradually increases from the direction close to the substrate to the direction far away from the substrate, and the columnar crystals of the α-Ta layer are completely broken by the α-Ta-N layer and do not extend to the α-Ta-N layer or the adjacent Ta layer.

[0053] The coating hardness was tested according to GB / T 4340.1-2009 "Metallic materials - Vickers hardness test - Part 1: Test method", and the coating adhesion was evaluated by the scratch test. The α-Ta / α-Ta-N coating has a hardness of 950 HV and a scratch test adhesion Lc2 > 92 N.

[0054] Figure 3 The image shown is a cross-sectional HRTEM image of Example 1, taking the HRTEM image of the α-Ta layer as an example. The upper right corner is a magnified view, and the lower right corner is the inverse Fourier transform result of the magnified view. According to Figure 3 The lattice mismatch between the α-Ta layer and the α-Ta-N layer is calculated to be 1.4%.

[0055] The nitrogen content in the α-Ta-N layer is 8.2 at.

[0056] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 2:1, the hardness of the α-Ta layer is 550 HV, and the hardness of the α-Ta-N layer is 2650 HV.

[0057] The crystallinity of the α-Ta-N layer is lower than that of the α-Ta layer.

[0058] Figure 4 The image shows the HRC indentation pattern of the coating in Example 1 at 150 kgf. It indicates that the coating around the HRC indentation at 150 kgf did not peel off, but only had radial cracks, and was rated as HF 1. Figure 5 The 10 kgf Vickers indentation of Example 1 demonstrates that the coating has no radial cracks in the 10 kgf Vickers indentation.

[0059] Example 2

[0060] The difference from Example 1 is as follows:

[0061] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 20 alternating layers; the thickness of a single α-Ta layer is 1000 nm and the thickness of a single α-Ta-N layer is 250 nm.

[0062] In the S3 alternating layer deposition step: the coating substrate was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity of 99.96 wt%. The deposition atmosphere pressure was 0.68 Pa, and the α-Ta-N layer deposition atmosphere was a mixture of argon and nitrogen; the flow rate ratio of argon to nitrogen in the mixed atmosphere was 85:1. The time without nitrogen introduction was 10 min, and the time with nitrogen introduction was 2.5 min.

[0063] The α-Ta / α-Ta-N coating has a hardness of 850 HV and a scratch adhesion strength L. c2 >89 N.

[0064] The lattice mismatch between the α-Ta layer and the α-Ta-N layer is 1.35%.

[0065] EDS analysis showed that the nitrogen content in the α-Ta-N layer was 7.9 at.

[0066] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 4:1.

[0067] like Figure 6 and Figure 7 As shown, the coating around the HRC indentation at 150 kgf showed no peeling, only radial cracks, and was rated as HF1. ​​The coating showed no radial cracks at the 10 kgf Vickers indentation.

[0068] Example 3

[0069] The difference from Example 1 is as follows:

[0070] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 48 alternating layers; the thickness of a single α-Ta layer is 125 nm, and the thickness of a single α-Ta-N layer is 125 nm.

[0071] In the S2 sub-base deposition step: deposition atmosphere pressure 0.8 Pa, target peak power density 2100 W / cm³ 2 The time for both nitrogen-free and nitrogen-introduced gas is 2 minutes.

[0072] The α-Ta / α-Ta-N coating has a hardness of 1025 HV and a scratch adhesion strength of L. c2 >70 N.

[0073] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 1:1.

[0074] The coating around the HRC indentation at 150 kgf showed no peeling, only radial cracks, and was rated as HF 1. The coating showed no radial cracks at the 10 kgf Vickers indentation.

[0075] Example 4

[0076] The difference from Example 1 is as follows:

[0077] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 24 alternating layers; the thickness of a single α-Ta layer is 250 nm, and the thickness of a single α-Ta-N layer is 250 nm. The time for both nitrogen-free and nitrogen-introduced gas is 2.5 min.

[0078] The α-Ta / α-Ta-N coating has a hardness of 1150 HV and a scratch adhesion strength of L. c2 >65 N.

[0079] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 1:1.

[0080] The coating around the HRC indentation at 150 kgf showed no peeling, only radial cracks, and was rated as HF 1. The coating showed no radial cracks at the 10 kgf Vickers indentation.

[0081] Example 5

[0082] The difference from Example 1 is as follows:

[0083] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 6 alternating layers; the thickness of a single α-Ta layer is 2000 nm, and the thickness of a single α-Ta-N layer is 2000 nm.

[0084] In the S3 alternating layer deposition step: the target peak power density is 3000 W / cm³. 2 The ratio of nitrogen to argon in the α-Ta-N layer was 75:1. The time for both nitrogen-free and nitrogen-introduced gas was 18 min.

[0085] The α-Ta / α-Ta-N coating has a hardness of 875 HV and a scratch adhesion strength of L. c2 >81 N.

[0086] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 1:1.

[0087] The coating around the HRC indentation at 150 kgf showed no peeling, only radial cracks, and was rated as HF 1. The coating showed no radial cracks at the 10 kgf Vickers indentation.

[0088] Example 6

[0089] The difference from Example 1 is as follows:

[0090] The alternating layers consist of alternating α-Ta layers and α-Ta-N layers, with a total of 60 alternating layers.

[0091] The atmosphere in S1 is a combination of argon and hydrogen.

[0092] In S2, the bottom layer deposition was performed with a deposition atmosphere pressure of 0.8 Pa, a bias voltage of 600 V, and a target peak power density of 2000 W / cm³. 2 ;

[0093] In S3, alternating layer deposition was performed: depositional atmosphere pressure was 0.8 Pa, and target peak power density was 2400 W / cm³. 2 In a mixed atmosphere of argon and nitrogen, the flow rate ratio of argon to nitrogen is 90:1. The target-substrate distance is 85 mm.

[0094] The α-Ta / α-Ta-N coating has a hardness of 860 HV and a scratch adhesion strength of L. c2 >80 N.

[0095] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 1:1.

[0096] The coating around the HRC indentation at 150 kgf showed no peeling, only radial cracks, and was rated as HF 1. The coating showed no radial cracks at the 10 kgf Vickers indentation.

[0097] Comparative Example 1

[0098] To further demonstrate the beneficial effects of the proposed solution, the inventors have provided typical comparative examples here.

[0099] The difference from Example 1 is as follows:

[0100] The alternating layers consist of alternating α-Ta and α-Ta-N layers, with a total of 10 alternating layers; the thickness of a single α-Ta layer is 1000 nm, and the thickness of a single α-Ta-N layer is 1500 nm.

[0101] The α-Ta / α-Ta-N coating has a hardness of 1200 HV and a scratch adhesion strength of L. c2 ~58 N.

[0102] The thickness ratio of the α-Ta layer to the α-Ta-N layer is 1:1.5.

[0103] like Figure 8 As shown, radial cracks and significant peeling appeared in the coating around the HRC indentation at 150 kgf, which can be rated as HF 4 according to VDI 3198 criteria. Because the thickness ratio of the α-Ta layer to the α-Ta-N layer does not conform to the specifications of this invention, it exhibits worse adhesion and load-bearing capacity compared to all the aforementioned embodiments.

[0104] Comparative Example 2

[0105] To further demonstrate the beneficial effects of the proposed solution, the inventors have provided typical comparative examples here.

[0106] The difference from Example 1 is as follows:

[0107] In the mixed atmosphere of argon and nitrogen, the flow rate ratio of argon to nitrogen is 30:1.

[0108] The α-Ta / α-Ta-N coating has a hardness of 1180 HV and a scratch adhesion strength of L. c2 ~52 N.

[0109] Radial cracks and significant peeling appeared in the coating around the HRC indentation at 150 kgf, which, according to VDI 3198 criteria, can be rated as HF 3. Figure 9 As shown, radial and circumferential cracks appeared in the 10 kgf Vickers indentation of the coating, and the fracture toughness was significantly reduced. Because the argon to nitrogen flow ratio of 30:1 did not conform to the specifications of this invention, trace amounts of nitride (FCC-TaN) were precipitated. The change in crystal structure led to a significant increase in lattice mismatch, resulting in poorer adhesion and load-bearing capacity compared to all the aforementioned embodiments.

[0110] Comparative Example 3

[0111] To further demonstrate the beneficial effects of the proposed solution, the inventors have provided typical comparative examples here.

[0112] The difference from Example 1 is as follows:

[0113] In the mixed atmosphere of argon and nitrogen, the flow ratio of argon to nitrogen is 1:1;

[0114] The Ta-N layer is a single δ-TaN phase with a hardness of 3500 HV;

[0115] The α-Ta / α-Ta-N coating has a hardness of 1805 HV and a scratch adhesion strength of L. c2 ~42 N.

[0116] Radial cracks and significant peeling appeared in the coating around the HRC indentation at 150 kgf, which can be rated as HF 4 according to VDI 3198 criteria. Significant radial cracks appeared in the coating at 10 kgf Vickers indentation. Due to the excessively high hardness of the Ta-N layer, exceeding the limits set in this invention, the deformation difference between adjacent layers under external force was too large, resulting in greater interfacial stress and inducing crack initiation and propagation. Compared to all the aforementioned embodiments, it exhibits poorer adhesion and load-bearing capacity.

[0117] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A high-load-bearing and high-bonding α-Ta / α-Ta-N coating, characterized in that: 1) The α-Ta / α-Ta-N coating includes a primer layer and an alternating layer, and the alternating layer is connected to the substrate through the primer layer; 2) The alternating layers are composed of α-Ta layers and α-Ta-N layers alternately, and the number of alternating layers is ≥ 6; 3) The crystal structures of the α-Ta layer and the α-Ta-N layer are both single body-centered cubic structures, and the α-Ta-N layer has no columnar crystal characteristics and is a solid solution phase.

2. The high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 1, characterized in that: The grain size of the horizontal cross section of the columnar crystals of the α-Ta layer gradually increases from the direction close to the substrate to the direction away from the substrate, and the columnar crystals of the α-Ta layer are completely interrupted by the α-Ta-N layer and will not extend to the α-Ta-N layer or the adjacent Ta layer.

3. The high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 1 or 2, characterized in that: The α-Ta / α-Ta-N coating has a hardness of 800-1800 HV, a scratch method bonding force Lc2>60 N, and a Vickers indentation under 10 kgf without radial cracks.

4. The high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 1 or 2, characterized in that: The lattice mismatch between the α-Ta layer and the α-Ta-N layer is less than 3%, and the crystallinity of the α-Ta-N layer is lower than that of the α-Ta layer.

5. The high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 1 or 2, characterized in that: The N content in the α-Ta-N layer is 1.0 to 9.9 at %.

6. The high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 1 or 2, characterized in that: The thickness ratio of the α-Ta layer to the Ta-N layer is (1-8):1, the hardness of the α-Ta layer is 500-750 HV, and the hardness of the Ta-N layer is 1500-2800 HV.

7. The method for preparing the high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to any one of claims 1 to 6, characterized in that: The steps include: S1. Cleaning: plasma cleaning the base material using arc enhanced glow discharge technology; S2. Base deposition: High-power pulsed magnetron sputtering technology superimposed with DC magnetron sputtering technology, using a tantalum target with a purity of ≥99.95 wt% to prepare the base layer, the deposition atmosphere pressure is 0.5-1.0 Pa, and the target peak power density is ≥1800 W / cm 2 ; S3, alternating layer deposition: high-power pulsed magnetron sputtering technology superimposed on DC magnetron sputtering technology, using a tantalum target with a purity of ≥99.95 wt% to prepare the coating body, the bias voltage is less than S2, the deposition atmosphere pressure is 0.5-1.0 Pa, and the target peak power density is ≥1800 W / cm 2 .

8. The method for preparing the high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 7, characterized in that: In S1, the temperature of plasma cleaning is ≤200 °C, the time is 5 to 20 min, the ratio of anode current to cathode current in arc enhanced glow discharge technology is greater than 1, and the atmosphere is argon or a combination of argon and hydrogen.

9. The method for preparing the high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 7, characterized in that: In S2, the average current ratio of DC magnetron sputtering / high power pulsed magnetron sputtering is ≤0.8, the temperature is ≤200 °C, the bias voltage is 400-1000 V, and the atmosphere is argon.

10. The method for preparing the high-load-bearing and high-bonding-strength α-Ta / α-Ta-N coating according to claim 7, characterized in that: In S3, the average current ratio of DC magnetron sputtering / high power pulsed magnetron sputtering is ≤0.8, the temperature is ≤350 °C, the bias voltage is 0-300 V, and the target-substrate distance is 80-100 mm; Preferably, in S3, the deposition of Ta and Ta-N layers is achieved by adjusting the ratio of nitrogen to argon, the deposition atmosphere of the Ta layer is argon, and the deposition atmosphere of the Ta-N layer is a mixed atmosphere of argon and nitrogen; Preferably, in the mixed atmosphere of argon and nitrogen, the flow ratio of argon to nitrogen is 75:1-100:1.

Citation Information

Patent Citations

  • High-hardness wear-resistant thermal-shock-resistant thick tantalum coating and preparation method thereof

    CN107130212A

  • TiAlN / W2N multi-layer coating with high hardness and high corrosion resistance and preparation method thereof

    CN108517487A

  • Multi-layer high-corrosion-resistance coating for bipolar plate of PEM electrolytic tank and preparation method of multi-layer high-corrosion-resistance coating

    CN118109785A

  • High-bearing high-binding-force pure alpha-Ta coating and preparation method thereof

    CN118207505A

  • Preparation method of ablation-resistant refractory metal tantalum and nitride multilayer coating of ablation-resistant refractory metal tantalum

    CN118422145A